Feed supplementation of lactating N'Dama cows under village husbandry - Little, D.A.; Wassink, G.J.; Agyemang, K.; Leperre, P.; Janneh, L.; Badjie, B. (1994)
Groups of lactating N'Dama cows maintained under traditional husbandry conditions were given dry season supplements of locally available oil seed residues to establish nutritional recommendations for improving livestock productivity in the sub-humid zone of West Africa. In one experiment cows were given 0 or 1 kg cotton seed head-1 day -1 for the last five months of the dry season in three Gambian villages. In a second experiment cows were given a total of 90 kg sesame cake over the last six months of the dry season, at rates of 1 kg day-1 for the first or last three months, or 0.5 kg day-1 throughout. During this period the provision of supplements produced significant overall average increases exceeding 60 percent in both milk offtake for human consumption and calf growth. Maternal liveweight losses were reduced by a mean of 30 percent. Concomitant significant increases in postpartum resumption of reproductive activity (two-to three-fold) and reduced calf mortality also occurred, while evidence was obtained that the improved diet better enabled the animals to withstand the effects of trypanosome infections. It was demonstrated that the dry-season provision of oil seed residues to lactating N'Dama cows in this environment can be expected to produce an extra litre of milk offtake, 260 g calf growth, and 380 g maternal liveweight gain kg-1 crude protein supplied , in addition to the improvement in other productivity characteristics. The second experiment showed much greater efficiency of resource use when fed more slowly for the longer period, and the economic benefits of such interventions appear to be substantial.